Thoracic Anesthesia and Cross Field Ventilation for Tracheobronchial Injuries: A Challenge for Anesthesiologists - Sankalp Sehgal; Joshua C. Chance; Matthew A. Steliga (Case Reports in Anesthesiology)
Tracheobronchial injuries are rare but life threatening sequel of blunt chest trauma. Due to the difficult nature of these injuries and the demanding attributes of the involved surgery, the anesthesiologist faces tough challenges while securing the airway, controlling oxygenation, undertaking one-lung ventilation, maintaining anesthesia during tracheal reconstruction, and gaining adequate postoperative pain control. Amongst the few techniques that can be used with tracheobronchial injuries, cross field ventilation is a remotely described and rarely used technique, especially in injuries around the carina. We effectively applied cross field ventilation in both our cases and the outcome was excellent.